Fall of Giants - Ken Follett (UK Pan Books, 2011)
Follows the fates of five interrelated families--American, German, Russian, English, and Welsh--as they move through the dramas of the First World War, the Russian Revolution, and the struggle for women's suffrage.
An Epic of Love, Hatred, War and Revolution
Keywords: Literature (3GdCOHs; General -- Fiction; Twentieth century; World War, 1914-1918 -- Fiction